In Vitro Bioconversion of Pyruvate to n-Butanol with Minimized Cofactor Utilization - Reiße, Steven; Haack, Martina; Garbe, Daniel; Sommer, Bettina; Steffler, Fabian; Carsten, Jörg; Bohnen, Frank; Sieber, Volker; Brück, Thomas (Frontiers in Bioengineering and Biotechnology, 2016)
Due to enhanced energy content and reduced hygroscopicity compared to ethanol, n-butanol is flagged as a next generation biofuel and platform chemical. In addition to conventional cellular systems, butanol bioproduction by enzyme cascades is gaining momentum due to simplified process control. In contrast to other bio-based alcohols like ethanol and isobutanol, cell-free butanol biosynthesis from the central metabolic intermediate pyruvate involves co-factors (NAD(P)H, CoA) and acetyl-CoA dependent intermediates, which complicates redox and energy balancing of the reaction system. We have devised a biochemical process for cell-free butanol production that only involves three enzyme activities, thereby eliminating the need for acetyl-CoA. Instead the process utilizes only NADH as the sole redox mediator. Central to this new process is the amino acid catalyzed enamine – aldol – condensation, which transforms acetaldehyde directly into crotonaldehyde. Subsequently, crotonaldehyde is reduced to n-butanol applying a 2-enoate reductase and an alcohol dehydrogenase, respectively. In essence, we achieved conversion of the platform intermediate pyruvate to n-butanol utilizing a biocatalytic cascade comprising only three enzyme activities and NADH as reducing equivalent. With reference to previously reported cell-free n-butanol reaction cascades, we have eliminated five enzyme activities and the requirement of CoA as co-factor. Our proof-of-concept demonstrates that n-butanol was synthesized at neutral pH and 50 °C. This integrated reaction concept allowed GC detection of all reaction intermediates and n-butanol production of 148 mg L-1 (2 mM), which compares well with other cell-free butanol production processes.